Book Review - Zulfiqar Ali (Journal of Political Studies, 2012)
Umbreen Javaid in her recent study seeks to explore the tremendous strategic importance of South Asia having two rival nuclear powers, India and Pakistan, and contrasts the same with this region being poverty-stricken, underdeveloped, fragile and conflict-ridden simultaneously. This work addresses the relations between India and Pakistan, marked by tensions and lack of regional co-operation thus hindering the overall growth in the region. It also discusses the prospects of peace and stability in South Asia after nuclearization of India and Pakistan. The strategic significance of this region is highlighted by the location of powerful neighbors like China and the Middle East